2018
DOI: 10.1111/hsc.12532
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of rural health and human service practitioners following suicide prevention training programme in Australia: A thematic analysis

Abstract: There are well-established training programmes available to support health and human services professionals working with people vulnerable to suicide. However, little is known about involving people with lived experience in the delivery of suicide prevention training with communities with increased rates of suicide. The aim of this paper was to report on a formative dialogical evaluation that explored the views of health and human services workers with regard to a suicide prevention training programme in regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Our research has indicated the value of co‐producing suicide prevention training with a lived experience trainer (Jones et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our research has indicated the value of co‐producing suicide prevention training with a lived experience trainer (Jones et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…10 We want to provide a rationale for recommending that researchers who have used qualitative methods use good practice guidelines on reporting the outcomes of qualitative research. Qualitative approaches can help answer research questions and shine a light on issues that other methodological approaches cannot answer, 11 for example asking nurses how they can be better supported to prescribe mental health medicines in the bush 12 or asking rural health workers how we can deliver more appropriate suicide prevention to rural and remote health care workers training, 13 describing experiences of family members with community palliative care 14 and understanding better what it is like to work as a health care professional in remote Australia. 15 The importance of standards and rigour around qualitative research has been discussed for many years.…”
mentioning
confidence: 99%
“…2013; Jones et al . 2018). Some authors noted that participants were motivated to attend the workshops and training, which potentially may have skewed their responses (Gryglewicz et al .…”
Section: Resultsmentioning
confidence: 99%